(untitled) (Docentes 2.0 Journal, 2025)
Communication skills among primary school students are a fundamental aspect of the educational environment and are reinforced through strategies within a reading plan established by the Peruvian ministries of education. The objective of this research was to examine how the Reading Plan influenced the development and strengthening of communication skills among primary school students in Peru. It was conducted within the interpretive paradigm, using a systematic method, with a qualitative approach, a narrative design, and a cross-sectional bibliographic and documentary approach. The PRISMA-ScR protocol was followed, with searches in prestigious scientific databases such as Scopus, SciELO, Web of Science (WOS), Redalyc, ResearchGate, and Dialnet. This ensured the rigor and validity of the analysis of 15 scientific publications using documentary analysis techniques and systematic review matrix instruments. Based on the analysis, the Reading Plan, in its current form, constitutes a highly relevant pedagogical strategy with significant formative potential that has not yet been fully recognized or utilized in educational institutions in Peru. Far from being limited to a reading promotion tactic, its true strength lies in its configuration as a comprehensive pedagogical tool that fosters critical comprehension, reflective thinking, and effective language expression.